2000
DOI: 10.1111/j.1469-7793.2000.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of N‐type α1B and P/Q‐type α1A calcium channels by different G protein β subunit isoforms

Abstract: Using transient calcium phosphate transfection into the human embryonic kidney tsa‐201 cell line and subsequent whole‐cell patch‐clamp protocols, we examined the tonic modulation of cloned N‐ and P/Q‐type calcium channels by five different G protein β subunits via strong depolarizing voltage prepulses. For N‐ and P/Q‐type channels, the magnitude of inhibition was dependent on the Gβ subtype co‐expressed. Both the absolute and relative magnitudes of Gβ subunit‐induced inhibition of P/Q‐type channels differed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 33 publications
3
63
0
1
Order By: Relevance
“…Wild-type calcium channel cDNA constructs were supplied by Dr. Terry Snutch. The G protein cDNA constructs used were the same as those described by us previously (Arnot et al 2000;Feng et al 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type calcium channel cDNA constructs were supplied by Dr. Terry Snutch. The G protein cDNA constructs used were the same as those described by us previously (Arnot et al 2000;Feng et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…There are 5 known G␤ isoforms and 11 known G␥ isoforms (Betty et al 1998), and transient transfection studies have shown that different isoform combinations produce different inhibitory effects on Ca 2ϩ channels (Arnot et al 2000;Diversé-Pierluissi et al 2000;García et al 1998;Ruiz-Velasco and Ikeda 2000;Zhou et al 2000). In most cases, G␤␥ dissociates from channels when the membrane is depolarized (Boland and Bean 1993;Hille 1994;Zamponi and Snutch 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the rank order of inhibition produced by the five different Gβ subunits (Gβ [1][2][3][4][5] ), all paired with the same Gγ 2 subunit, differs for Ca V 2.1 and Ca V 2.2 channels. 103 In another study, point mutations on the Gβ 1 subunit had distinct effects on the inhibition of Ca V 2.1 and Ca V 2.2 channels. 104 Functional differences might also arise from variable interactions or crosstalk with other signaling pathways.…”
Section: Differential Voltage-dependent Inhibition Within the Ca V 2 mentioning
confidence: 97%
“…We have previously described the cloning of G␤ 5 from rat brain via reverse transcriptase-PCR (29). Using XhoI and KpnI sites, the G␤ 5 insert was excised from pGEM T-Easy and subcloned in-frame into pTrcHisA.…”
Section: Creation Of G␤ 5 In Ptrchisa (His 6 Fusion Construct)mentioning
confidence: 99%